Efficacy of mGlu2‐positive allosteric modulators alone and in combination with levetiracetam in the mouse 6 Hz model of psychomotor seizures. (6th February 2017) - Metcalf, Cameron S.; Klein, Brian D.; Smith, Misty D.; Pruess, Tim; Ceusters, Marc; Lavreysen, Hilde; Pype, Stefan; Van Osselaer, Nancy; Twyman, Roy; White, H. Steve
Summary: Objective: The metabotropic glutamate receptor subtype 2 (mGlu2 ) possesses both orthosteric and allosteric modulatory sites, are expressed in the frontal cortex and limbic structures, and can affect excitatory synaptic transmission. Therefore, mGlu2 is a potential therapeutic target in the treatment of epilepsy. The present study seeks to evaluate the anticonvulsant potential of mGlu2 ‐acting compounds. Methods: The anticonvulsant efficacy of two selective mGlu2 ‐positive allosteric modulators (PAMs) (JNJ‐42153605 and JNJ‐40411813/ADX71149) and one mGlu2/3 receptor agonist (LY404039) were evaluated alone and in combination with the antiseizure drug levetiracetam (LEV) in the mouse 6 Hz model. Results: In the 6 Hz (32 mA stimulus intensity) model, median effective dose (ED50 ) values were determined for JNJ‐42153605 (3.8 mg/kg), JNJ‐40411813 (12.2 mg/kg), and LY404039 (10.9 mg/kg). At the 44 mA stimulus intensity, ED50 values were determined for JNJ‐42153605 (5.9 mg/kg), JNJ‐40411813 (21.0 mg/kg), LY404039 (14.1 mg/kg), and LEV (345 mg/kg). In addition, subprotective doses of each mGlu2 ‐acting compound, administered in combination with various doses of LEV, were able to shift the 6 Hz 44 mA ED50 for LEV by >25‐fold. When JNJ‐42153605 was administered at varying doses in combination with a single dose of LEV (10 mg/kg), the potency of JNJ‐42153605 was increased 3.7‐fold. Similarly, when a moderately effective dose of LEV (350 mg/kg) was administered in combination with varying doses of JNJ‐40411813, the potency of JNJ‐40411813 was increased approximately 14‐fold. Plasma levels of JNJ‐40411813 and LEV were not different when administered alone or in combination, suggesting that increases in potency are not due to pharmacokinetic effects. Significance: These studies suggest a potential positive pharmacodynamic effect of mGlu2 ‐acting compounds in combination with LEV. If this effect is translated in a clinical setting, it can support a rational polypharmacy concept in treatment of epilepsy patients.